Acute Kidney Injury After Efavirenz/Tenofovir Disoproxil Fumarate/Emtricitabine (Atripla) Overdose. Issue 2 (April 2017) - Havenith, Thomas; Burger, David; Visschers, Maarten J.; Schippers, Jolanda; Oude Lashof, Astrid
Abstract : Abstract: We describe a patient with acute renal failure and irreversible kidney damage after an overdose with the fixed dose combination of efavirenz/tenofovir disoproxil fumarate/emtricitabine (Atripla). The acute kidney injury was most probably caused by tenofovir. Efavirenz and emtricitabine seemed relatively safe in overdose. The pharmacokinetics in overdose of all 3 drugs and the effect of hemodialysis on the tenofovir clearance were studied by measuring the plasma concentrations and by the use of clinical pharmacokinetic software.